Acute-on-chronic liver failure: current concepts on definition, pathogenesis, clinical manifestations and potential therapeutic interventions. (August 2011) - Laleman, Wim; Verbeke, Len; Meersseman, Philippe; Wauters, Joost; van Pelt, Jos; Cassiman, David; Wilmer, Alexander; Verslype, Chris; Nevens, Frederik
In recent years, acute-on-chronic liver failure has been recognized as a specific clinical form of liver failure associated with cirrhosis. The syndrome refers to an acute deterioration of liver function and subsequently of other end organs over a period of weeks following a precipitating event in a patient with previously well- or reasonably well-compensated cirrhosis. These precipitating events include either an indirect (e.g., variceal hemorrhage, sepsis) or a direct (e.g., drug-induced) hepatotoxic factor. The short-term mortality for this condition is more than 50%. At present, considerable efforts are ongoing to better characterize the syndrome, to gain further insight into its pathophysiology and to optimize therapy. This article aims to highlight the current concepts of these various aspects.